Demand elasticity of import nuts in Korea - Xiaoling Zhu (Heliyon, 2023)
This paper empirically analyzes import demand for nuts in Korea using Almost Ideal Demand System (AIDS). Six budget shares and prices demand equations for nuts group: almond, pistachio, walnut, cashew, hazelnut and macadamia are analyzed during the period 2009 to 2019. Empirical results show that all uncompensated own-price elasticities are negative, walnut and pistachio are own-price elastic while almond, cashew, hazelnut and macadamia are own-price inelastic. Uncompensated cross-price elasticities indicate that nuts have both complementary and substitutable relationships. Expenditure elasticities reveal that all import nuts are expenditure inelastic and they can be considered as necessary goods in Korea. Our research can help related to policy decision for the demand of Korea import nuts.